Research and development of designs of the equipment for classifying the materials with particles - Gunsen, Ganbaatar; Yadam, Renchinvanjil (Mongolian Journal of Agricultural Sciences, 2021)
There are studies showing that 10% of the total energy generated in the world is spent on crushing and sifting and sorting processes in agricultural and mining sectors. 52.7% of the total mining industries extracts metal ores, 36.3% of them extracts coal and agricultural sector plants wheat and crops on the 350 thousand hectares of land per year an average. It can be seen that there is a need for sorting the materials with particles in these sectors. According to the needs, the energy expenditure is high and the devices and equipment used still maintaining their traditional designs and makes. The process of sorting out the materials with particles is sifted by the flat surfaced, trommel shaped, and cylindrical mesh surfaces positioned in vertical axis. The above methods are still in use, which becomes the basis of mechanical sifting methods. Therefore, the researchers continue to work on perfecting the above methods. The goal of this research work is to survey and determine the possibility of the changes in the designs of sifting equipment with the trommels can improve the influences that are created during the sifting process, the efficiency of sifting and the productivity of device or equipment. By this research work, with the purpose to improve the parameters of sifting of materials with particles, we will change the design of cylindrical trommel of the cross trommel sieve, which is often used in the sifting process to axle to its axis, and in order to confirm the results of experiment by determining the CAD analysis of axle trommel and the movement of one particle inside of it using the ADAMS software, the experiment on the real equipment shall be rationalized by putting into the mathematic modeling, develop the physical modeling using the “EDEM solution” software and process the results.